Les archives, un outil dans la construction d’un rapport de force féministe : l’exemple d’un groupe féministe et syndical - Maëva Ballon; Flaz Torres (Glad!)
A feminist group within a union, and the production of records, understood as traces of our militant activity, has a triple political dimension. As material tools for the description and representation of political and feminist action, records inscribe in time, the reality and the materiality of our commitments and our achievements. Despite the fact that the context is a social and union one, it is nonetheless marked by relationships of male domination in its functioning and militant activity. Records and archives therefore constitute fundamental sources of legitimization of our feminist actions. Finally, the process of production of our group's records constitutes in itself a feminist practice.Through examples of activist objects, digital tools and formats we illustrate the construction of a singular feminist power struggle. The conditions of creation, and the uses and the methods of preservation of our archives demonstrate deliberate political practices, all with the objective of fighting against the patriarchy.